2021
DOI: 10.1016/s2666-7568(21)00177-x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related disparities in diabetes risk attributable to modifiable risk factor profiles in Chinese adults: a nationwide, population-based, cohort study

Abstract: Background National investigations of age-specific modifiable risk profiles for diabetes are crucial to promote personalised strategies for the prevention and control of diabetes, particularly in countries such as China, which is experiencing both a diabetes epidemic and a rapidly ageing population. We aimed to examine the associations of 12 potentially modifiable socioeconomic, lifestyle, and metabolic risk factors with diabetes in a nationwide prospective cohort of Chinese adults across four age groups. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 23 publications
3
15
0
1
Order By: Relevance
“…When possessing the same number of risk category, adults younger than 55 years were at higher risk of diabetes than their older counterparts. Similar age‐related decrease in diabetes risk associated with multiple risk factors such as obesity and dyslipidemia were observed in a recent study of 93 781 Chinese adults aged ≥40 years 41 . Besides, a genome‐wide association study in the UK Biobank identified different genetic variations associated with age at diagnosis of diabetes, supporting the hypothesis that the pathogenesis of diabetes changes with age 42 …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…When possessing the same number of risk category, adults younger than 55 years were at higher risk of diabetes than their older counterparts. Similar age‐related decrease in diabetes risk associated with multiple risk factors such as obesity and dyslipidemia were observed in a recent study of 93 781 Chinese adults aged ≥40 years 41 . Besides, a genome‐wide association study in the UK Biobank identified different genetic variations associated with age at diagnosis of diabetes, supporting the hypothesis that the pathogenesis of diabetes changes with age 42 …”
Section: Discussionsupporting
confidence: 79%
“…Similar age‐related decrease in diabetes risk associated with multiple risk factors such as obesity and dyslipidemia were observed in a recent study of 93 781 Chinese adults aged ≥40 years. 41 Besides, a genome‐wide association study in the UK Biobank identified different genetic variations associated with age at diagnosis of diabetes, supporting the hypothesis that the pathogenesis of diabetes changes with age. 42 …”
Section: Discussionmentioning
confidence: 67%
“…We suggested that education level may affect the behavioral pattern of follow‐up—patients with higher education level (high school and above) may have better treatment compliance, resulting in better metabolic outcomes. Recently, our group revealed that less education (lower than high school) is one of the socioeconomic risk factors which contribute to the diabetes risk in adults 22 . This work with real‐world, large sample data extended previous research on the association between follow‐up frequency and glycemic control, and we evaluated more additional metabolic parameters.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, our group revealed that less education (lower than high school) is one of the socioeconomic risk factors which contribute to the diabetes risk in adults. 22 This work with real‐world, large sample data extended previous research on the association between follow‐up frequency and glycemic control, and we evaluated more additional metabolic parameters. Our results demonstrate that HFF was associated with greater improvements in metabolic outcomes, including FBG, HbA1c, blood pressure, and cholesterol level in HFF participants.…”
Section: Discussionmentioning
confidence: 81%
“…Metabolic health generally decreases with advancing age (e.g., due to aging per se and due to behavioral changes such as decreased physical activity), which is reflected by an increased risk of dyslipidemia and insulin insensitivity at higher age (X. Liu et al, 2018; T. Wang et al, 2021a). Hence, it can be hypothesized that cannabinoid signaling and CB 1 expression is responsive to ageing in a metabolic tissue such as skeletal muscle.…”
Section: Cannabinoid System and Muscle Homeostasis: Paths And Challengesmentioning
confidence: 99%